ANALYSIS AND OPTIMIZATION OF DYNAMIC OUTPUT SHAFT STRUCTURE BASED ON FINITE ELEMENT METHOD - LI YunPeng; CHENG ZiLi; ZHANG HongTao; WAN GuoWei (Jixie qiangdu)
The output shaft is one of the core components of the gearbox of an oil rig,The reliability of the output shaft directly affects the service life and economic benefit of the oil rig. In this paper,the stress analysis of the structure of the original output shaft is carried out by using the finite element method; The optimization and improvement scheme is put forward,and the stress of the output spindle before and after the improvement is compared and analyzed,According to the analysis results,the final improvement scheme of the output shaft is determined,The results show that the safety factor of the improved output shaft is significantly improved,The modal of the output shaft is analyzed by finite element method,It is verified that the working speed of the output shaft is within the safe range. The research in this paper has certain guiding significance to improve the performance of oil rig output shaft.